Meningkatkan Keterampilan Menulis Puisi dengan Model Think Talk Write - Rahma Yulianti; Hasnah Faizah AR; Elvrin Septyanti (Universitas Indraprasta PGRI, 2023)
This study aims to determine the improvement of poetry writing skills with the Think Talk Write model. The method used in this research is a class action research design (CAR). This research was conducted in two phases, which consisted of planning, implementing, observing, and reflecting. Data collection techniques used in this study were tests, observations, and interviews.The data analysis technique used in this study uses quantitative methods accompanied by descriptive analysis. The results showed that the poetry test results experienced an increase in pre-cycle learning, cycle I and cycle II. The average value of the poetry test class in the pre-cycle was 60.21, the first cycle averaged 66.86, and the second cycle averaged 76.04. Improving the learning process of students who take part in learning is even more optimal before and after activities compared to cycle I and cycle II activities.Keywords: Poetry writing skills, think talk write